At the precipice : Americans north and south during the secession crisis - Bowman, Shearer Davis (Littlefield history of the Civil War era., 2010)
Bowman explores the different ways in which Americans, North and South, black and white, understood their interests, rights, and honor during the secession period. He examines the lives and thoughts of key figures and provides an especially vivid glimpse into what less famous men and women in both sections thought about themselves and the worlds in which they lived, and how their thoughts informed their actions during this time. Both sides glorified the Declaration of Independence and the Constitution of the United States, yet they interpreted those sacred documents in markedly different ways and held very different notions of what constituted "American" values.